THE EFFECT OF NATURAL READER IN THE TEACHING OF ORAL READING FLUENCY - Saiful, Saiful (English Education:Journal of English Teaching and Research, 2016)
Oral reading fluency is important skill that all readers need to develop, because those who has oral reading fluency are assumed to have the skill of reading comprehension and accuracy in delivering the speech. Natural Reader software is a professional text reader that converts any text into spoken words. In this quasi-experimental research applying non-randomized control group design pretest-posttest, the data used were interval data because they were taken from students’ scores of oral reading fluency test.This research was conducted in the English department of a College of Teacher Training and Education in Blitar. Group (1) consisted of 32 students taught using the natural reader software (experimental group) and Group (2) consisted of 35 students taught without using the natural reader software (control group). The control group simply attended in their ordinary classroom without using natural reader software and participated in instruction programs assigned by the lecturer in the classroom. The experimental group attended in the computer lab and listened to the text as it was read by natural reader software. This study revealed that the Natural Reader software could significantly prove that the students was able to read more accurately and at a more appropriate pace using instruction using natural reader software. By using natural reader software, the student could easily have frequently chances to listen the words read by the native speakers as a reader model at normal speed and repeat the copied reading text up to they were able to read fluently as the reader model read the text.